A planning system based on Markov decision processes to guide people with dementia through activities of daily living. - Boger, J.
Older adults with dementia often cannot remember how to complete activities of daily living and require a caregiver to aid them through the steps involved. The use of a computerized guidance system could potentially reduce the reliance on a caregiver. This paper examines the design and preliminary evaluation of a planning system that uses Markov decision processes (MDPs) to determine when and how to provide prompts to a user with dementia for guidance through the activity of handwashing. Results from the study suggest that MDPs can be applied effectively to this type of guidance problem. Considerations for the development of future guidance systems are presented
Keywords: MDP; Markov decision process; Autonomous guidance; Computerized guidance system; Daily living activities; Dementia; Handwashing; Older adults; Planning system